Litigating Cross-Border Aboriginal Title Claims in Canada: The Possibility (and Necessity) of a Federal Legislative Response to Newfoundland and Labrador (Attorney General) v. Uashaunnuat (Innu of Uashat and of Mani-Utenam) - Cossette-Lefebvre, Étienne (McGill Law Journal / Revue de droit de McGill, 2021)
There are many Indigenous peoples in Canada who have occupied, and continue to occupy today, traditional territories that straddle provincial borders. The decision of the Supreme Court of Canada in Newfoundland and Labrador (Attorney General) v. Uashaunnuat (Innu of Uashat and of Mani-Utenam) illustrates the practical difficulties faced by the Indigenous peoples in Canada who seek to claim Aboriginal rights in a single traditional territory that straddles provincial borders. Because of provincial Crown immunity, Indigenous peoples who wish to obtain a declaration of Aboriginal title that is binding on all the provincial Crowns concerned over a single traditional territory that straddles provincial borders have no choice but to bring proceedings in the courts of all the provinces concerned. This seems particularly unfair, especially since provincial borders were imposed on Indigenous peoples without regard for their pre-existing social organization. Forcing Indigenous peoples to bring multiple claims in multiple jurisdictions is also a threat to access to justice. In this article, I suggest amendments to the Federal Courts Act that would provide the Indigenous peoples in Canada who wish to litigate cross-border Aboriginal title claims with a forum in which all the parties necessary to resolve the issues fairly, including all the provincial Crowns concerned, could be summoned as defendants, and in which a declaration of Aboriginal title, binding on all such defendants, could be sought.